AUDIT EVALUATION OF EFFECTIVENESS OF BILL TRANSACTIONS IMPLEMENTATION - Liubezna, Iryna; Halushka, Nataliia (Journal of European Economy, 2017)
The theoretical and practical aspects of the audit of bill transactions are considered. The method of analytical evaluation of bill transactions with the consideration of the dual nature of a bill as a complex financial instrument (financial assets designated and not designated for resale and financial liability designated not for resale).